Awareness of muslim entrepreneur about halalan toyyiban food and beverages in Shah Alam and Klang / Muhammad Zaki Zakaria - Zakaria, Muhammad Zaki (2018)
Halalan Toyyiban for food and beverages had been a great issue discussed by people all over the world. The demand for halal food is not only from Muslim but also for non-Muslim. It is because food is something that we consume and can be a big effect in our daily life. The person who provide the food is very important to know. It is not something that people look away because the one who provide can affect the outcome of the food. The most important role in preparing food and beverages is entrepreneur. The demand not also look on who the entrepreneur is but it also look on how they prepare it and what did they use to prepare the food. All of this is a part of entrepreneur roles. Because of that, the research is focusing on entrepreneur about their awareness on halalan toyyiban food and beverages.